T-cell-depleted allogeneic bone marrow transplantation for acute leukaemia using Campath-1 antibodies and post-transplant administration of donor's peripheral blood lymphocytes for prevention of relapse. - Naparstek, E; Or, R; Nagler, A; Cividalli, G; Engelhard, D; Aker, M; Gimon, Z; Manny, N; Sacks, T; Tochner, Z (1995)
One hundred and forty-six patients with acute leukaemia (81 with ANLL and 65 with ALL) received allogeneic bone marrow transplantation from their fully matched siblings. 121 patients underwent T-cell depletion (TCD) using Campath 1 monoclonal rat anti-human lymphocyte (CDw52) antibodies; 67 with Campath 1M and 54 with Campath 1G isotypes. Patients were conditioned for transplant using either total body irradiation combined with chemotherapy (125 patients) or busulfan and cyclophosphamide (21 patients). 112 recipients of T-cell depleted allografts received in addition total lymphoid irradiation (TLI) for prevention of rejection. Engraftment of neutrophils (> 0.5 x 10(9)/l) and platelets (> 25 x 10(9)/l) occurred on days 15 and 18, and on days 18 and 20 in recipients of Campath 1M and Campath 1G treated marrows respectively. Rejection was documented in 6.8% of T-cell depleted transplants. Leukaemia relapse-free survival at 2 years was 83% for patients transplanted in first CR, 76% in second CR (P2 = 0.34) and 42% in advanced leukaemia (P2 = 0.009). 81 marrow recipients, 38 with Campath 1M and 43 with Campath 1G treated marrow, received post-transplant graded increments of donor's peripheral blood lymphocytes (PBL) to induce graft-versus-leukaemia (GVL) effects. Administration of donor's PBL was associated with clinically significant GVHD and with decreased relapse rate especially in patients with ALL. Our data suggest that in patients receiving marrow allografts depleted of T cells by Campath 1 monoclonal antibodies, rejection can be reduced by adequate pregrafting immunosuppression. In patients with advanced disease, post-transplant cell-mediated immunotherapy (CMI) using donor's PBL may be beneficial; however, further studies are needed to define the optimal schedule of CMI for safe and effective prevention of relapse following TCD bone marrow transplantation in malignant haematological diseases.